Fe(II)-Catalyzed Metal–Ligand Cooperative Approach for Selective C3-Alkylation of Indoles - Chakraborty, Subhajit; Mandal, Sutanuva; Paul, Nanda D. (Synlett, 2024)
Herein, we report a straightforward approach for synthesizing C3-alkylated indoles selectively via an iron-catalyzed alkylation of indoles using alcohols as the alkylating agents. A well-defined, air-stable, and easy-to-prepare Fe(II) catalyst of a redox-active tridentate arylazo scaffold was used as a catalyst. Various C3-alkylated indoles were prepared selectively in moderate to good isolated yields by coupling indoles with different substituted alcohols. The methodology is compatible with the gram-scale synthesis. Control experiments were performed to unveil the mechanism, which revealed that the alkylation reaction proceeds via borrowing-hydrogen pathway where the coordinated azo-aromatic ligand actively participates during catalysis, acting as an electron and hydrogen reservoir.
Keywords: iron catalysis; metal–ligand cooperativity; borrowing hydrogen approach; C3-alkylated indole; alcohols